Relationship between PM2.5 and Acute Respiratory Disease in a Colombian region: Generalized Additive Models - Grisales-Romero, Hugo; Montealegre, Nora; Piñeros, Juan Gabriel; Ospina, Dorian; Nieto, Emmanuel (Universidad y Salud, 2021)
Introduction: The harmful effect of fine particulate matter on the respiratory health of child and elderly populations is a concern for public health. Objective: To establish the effect of pollution by less than 2.5 μm in diameter (PM2.5) particulate matter on Acute Respiratory Disease (ARD) during 2008-2015 in children younger than 5 and adults older than 65 from the Metropolitan Area of the Aburrá Valley (Colombia), adjusting for meteorological and climate variables. Materials and methods: Ecological study with information from the air quality surveillance network and individual records of health providers. Generalized Additive Models were developed using smoothing spline Poisson models. The assessment of the association and confidence intervals were calculated for each distributed lag. Results: For each 10 µg/m3 increment in PM2 and the day 15 post-exposure, ARD cases increased significantly in populations who are younger than 5 and older than 65 in Envigado and Caldas (43.3% vs. 29.6%) and Medellín (13.2%), respectively. Conclusions: Daily respiratory events had a special frequency in Medellín and the municipalities of the southern region.